Extraction Socket Preservation Using Growth Factors and Stem Cells: a Systematic Review - Mindaugas Pranskunas; Pablo Galindo-Moreno; Miguel Padial-Molina (eJournal of Oral Maxillofacial Research)
Objectives:: To evaluate the reported literature on the use of stem cells or growth factors for post extraction treatment of the alveolar bone.